2000
DOI: 10.2134/jeq2000.00472425002900060041x
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Flow Constructed Wetland Performance at a Pennsylvania Campground and Conference Center

Abstract: A constructed wetland treatment system consisting of subsurface flow (SSF) wetland cells, sand filters, and final effluent wetlands was found to be effective in removing carbonaceous biochemical oxygen demand (CBOD) and total suspended solids (TSS) to below 30 and 10 mg L−1, respectively. Removal efficiency of total nitrogen (TN) loads improved from 60.1 to 88.5% over the 2‐yr study, primarily due to increased vegetation densities in the SSF wetland cells. In both years, parallel wetland treatment cells had si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The final effluent wetlands were not designed with a surface flow discharge, but were constructed so that the nitrified effluent would infiltrate the shallow riparian soils before reaching the receiving stream. Further details about the constructed wetland system are provided in Shannon et al (2000)…”
Section: Methodsmentioning
confidence: 99%
“…The final effluent wetlands were not designed with a surface flow discharge, but were constructed so that the nitrified effluent would infiltrate the shallow riparian soils before reaching the receiving stream. Further details about the constructed wetland system are provided in Shannon et al (2000)…”
Section: Methodsmentioning
confidence: 99%
“…As wetland sorption sites were saturated, phosphate removal was reduced (Tanner et al, 1998). Shannon et al (2000) showed removal of N to increase the second year and removal of phosphate to decrease the second year in an SF constructed wetland system. They attributed increased N removal to increased plant density and decreased phosphate removal to partial saturation of sorption sites.…”
mentioning
confidence: 97%
“…Constructed wetlands are a treatment method that contain and remove runoff chemicals by various processes including microbial degradation, plant uptake, sorption, chemical reactions, and volatilization. Constructed wetlands, using a subsurface flow (SF) gravel media, have recently been used to clean wastewater, primarily for N and P (Shannon et al, 2000; Tanner et al, 1998).…”
mentioning
confidence: 99%
“…However, the effectiveness at transforming and removing nitrogen and phosphorus is still very poor (USEPA, 1993;Reed et al, 1995). It has been reported recently that it is effective to use the combination of constructed wetlands and sand filters to treat septic tank effluent, polish, and nitrify secondary effluents (Schonborn, et al, 1996;Mander, et al, 1996;Gearheart 1999;Mahlum & Stalnacke, 1999;Shannon, et al, 2000). Boller et al (1993) studied laboratory and full-scale buried sand filters receiving septic tank wastewater under intermittent loading conditions.…”
Section: Sand Filtration Enhancement To Cw Effluentsmentioning
confidence: 99%
“…Since the coupling of CW and sand filters is a rather recent engineering practice to treat wastewater, there are very few reports of exhaustion problems and recovery methods for sand filtration under such conditions (Schonborn, et al, 1996;Shannon, et al, 2000).…”
Section: Maintenance Of Sand Filter Polishing Efficiencymentioning
confidence: 99%